Manajemen Perpustakaan Universitas Bengkulu Untuk Meningkatkan Pelayanan Sosial Terhadap Pemustaka Melalui Analisis Diagram Ishikawa - Alex Abdu Chalik; Yessilia Osira (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The purpose of this study is to get an overview and explanation of the various weaknesses of Bengkulu University Library management to improve social services to users by using Ishikawa diagram analysis consisting of Manpower/People, Materials, Methods/Processes, Machines/Equipment, Measurement/Minutes and Market/ User. This research method uses a qualitative descriptive method using a qualitative approach. Data were collected through in-depth interview techniques, observation, and documentation studies as well as Focus Group Discussion. The results of the study found that there were still many weaknesses in the administration, processing, circulation services and information technology. This weakness is related to human resources, materials and equipment, machinery/equipment, funds, and time and market (users). The problem that becomes this weakness is the lack of policy from the leadership to place quality human resources in the Bengkulu University Library UPT and provide opportunities for librarians and librarians to take part in internships and various training/workshops related to literature and the lack of budget allocations to repair and improve the quality of human resources, materials/equipment, machines/equipment, and other facilities and infrastructure that are damaged and not in accordance with the times